THE EFFECT OF ECONOMIC GROWTH AND DEMOGRAPHIC CONDITION ON CRIMINALITY IN EAST JAVA PROVINCE - Fani Novi Hariyanti; Rafael Purtomo Somaji; Regina Niken Wilantari (Jurnal Ekonomi dan Bisnis Airlangga, 2021)
Introduction: This study aims to determine how much the effect of economic growth and demographic conditions on the crime rate in East Java Province. This study is using secondary data for 6 years from 2013-2018.Methods: The data analysis method used in this study is panel data regression analysis method with the Fixed Effect Model (FEM) approach. The dependent variable used in this study is the crime rate, while the independent variables are economic and demographic growth, which includes population density and the number of poor people.Results: Based on the results of this study, it can be concluded that economic growth has a positive but insignificant relationship to the crime rate in East Java Province. Population density has a positive and significant relationship to the crime rate in East Java Province. Meanwhile, the number of poor people has a negative and significant relationship with the crime rate in East Java Province. The results of the study also show that economic growth, population density and the number of poor people have an effect and significant relationship on the crime rate in East Java Province.Conclusion and suggestion: This needs an equitable distribution of income and empowerment of human resources through improving educational facilities and infrastructure as well as skills so that productivity and community income increase. In addition, it is necessary to have equitable development and the provision of employment opportunities in each region so that population density is not concentrated in one or several areas.